Effectiveness of a multicomponent exercise training program for the management of delirium in hospitalized older adults using near-infrared spectroscopy as a biomarker of brain perfusion: Study protocol for a randomized controlled trial - Lozano-Vicario, Lucía; Zambom-Ferraresi, Fabiola; Zambom-Ferraresi, Fabricio; de la Casa-Marín, Antón; Ollo-Martínez, Iranzu; Sáez de Asteasu, Mikel L.; Cedeño-Veloz, Bernardo Abel; Fernández-Irigoyen, Joaquín; Santamaría, Enrique; Romero-Ortuno, Román; Izquierdo, Mikel; Martínez-Velilla, Nicolás (Frontiers in Aging Neuroscience, 2022)
Delirium is an important cause of morbidity and mortality in older adults admitted to hospital. Multicomponent interventions targeting delirium risk factors, including physical exercise and mobilization, have been shown to reduce delirium incidence by 30–40% in acute care settings. However, little is known about its role in the evolution of delirium, once established. This study is a randomized clinical trial conducted in the Acute Geriatric Unit of Hospital Universitario de Navarra (Pamplona, Spain). Hospitalized patients with delirium who meet the inclusion criteria will be randomly assigned to the intervention or the control group. The intervention will consist of a multicomponent exercise training program, which will be composed of supervised progressive resistance and strength exercise over 3 consecutive days. Functional Near-Infrared Spectroscopy (NIRS) will be used for assessing cerebral and muscle tissue blood flow. The objective is to assess the effectiveness of this intervention in modifying the following primary outcomes: duration and severity of delirium and functional status. This study will contribute to determine the effectiveness of physical exercise in the management of delirium. It will be the first study to evaluate the impact of a multicomponent intervention based on physical exercise in the evolution of delirium. Clinical trial registration ClinicalTrials.gov. identifier: NCT05442892 (date of registration June 26, 2022).